Dietary composition and prey selectivity of juvenile porcupine rays Urogymnus asperrimus. Issue 2 (28th May 2017) - Elston, C.; von Brandis, R. G.; Cowley, P. D.
Abstract : Fifty‐five juvenile porcupine ray Urogymnus asperrimus were collected in the isolated St Joseph Atoll, Seychelles. Stomach contents were sampled using non‐lethal gastric lavage to determine the dietary composition, degree of prey selectivity and whether sex or size affected their diet. Sediment samples were collected to quantify prey availability so that prey selectivity could be estimated. Two phyla (Sipuncula and Nemertea) and 11 polychaete and crustacean families were recorded in stomach contents. Juvenile U. asperrimus appeared to specialize on one polychaete family, Capitellidae, which was the most important prey item (index of importance = 35%). This polychaete family was also most abundant in the sediment samples and U. asperrimus are thus considered opportunistic predators. There was evidence of a size‐related shift in the crustacean families consumed by juvenile U. asperrimus . Data collected at this remote location provides important baseline ecological information that may prove useful in developing conservation strategies for this ecologically important species.